The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24098412
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and UV-Vis Spectra of Au3+ Complexes with Hydrazones Derived from Pyridoxal 5′-Phosphate: A DFT Study

Abstract: Gold(III) complexes with different ligands can provide researchers with a measure against pathogenic microorganisms with antibiotic resistance. We reported in our previous paper that the UV-Vis spectra of different protonated species of complexes formed by gold(III) and five hydrazones derived from pyridoxal 5′-phosphate are similar to each other and to the spectra of free protonated hydrazones. The present paper focuses on the reasons of the noted similarity in electron absorption spectra. The geometry of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 58 publications
(81 reference statements)
4
8
0
Order By: Relevance
“…Second, the calculated UV-Vis spectrum of the single protonated complexes of gold(III) with hydrazones has shown the worst agreement with the experimental spectra [40]. What is the reason behind this discrepancy?…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Second, the calculated UV-Vis spectrum of the single protonated complexes of gold(III) with hydrazones has shown the worst agreement with the experimental spectra [40]. What is the reason behind this discrepancy?…”
Section: Introductionmentioning
confidence: 97%
“…Our previous papers [39,40] were devoted to the study of the stability and structure of several gold(III) complexes with hydrazones derived from pyridoxal 5′-phosphate. PLP-derived hydrazones have received less attention with regard to their biological activity than PL hydrazones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morcoss et al [55] found promising anti‐cancer activity in benzimidazole‐hydrazone derivatives, while Erol et al [56] demonstrated good anti‐microbial activity against E. faecalis. Sajjan et al [57] explored parameters against anti‐cancer studies, and Pimenov et al [58] studied gold (III) condensation with hydrazones. Uddin et al [59] investigated the anti‐cancer properties of benzylidinemalononitrile and ethyl 2‐cyano‐3‐phenylacrylate derivatives using comprehensive in silico studies.…”
Section: Introductionmentioning
confidence: 99%